1976
DOI: 10.1063/1.432599
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the binding of an electron to a molecular dipole: LiCl−

Abstract: Ab initio calculations are carried out to determine the nature of the binding of the LiCl anion. The extra electron.is found to be in a predominantly nonbonding orbital on the lithium end of the molecule and the calculations predict an electron affinityu of LiCl of 0.54 eV. This is in good agreement with the experimental value of 0.61 eV, which has been recently determined by Carlsten, Peterson, and Lineberger. The ab initio results are discussed in light of the finite dipole model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 16 publications
8
69
1
Order By: Relevance
“…It has been shown that, within the Born-Oppenheimer (BO) approximation, a dipole moment greater than 1.625 D possesses an infinite number of bound anionic states, [47][48][49][50][51] although the more practical critical value required to experimentally observe a dipole-bound anion was found to be slightly larger, about 2.5 D. 43,52 Jordan and Luken demonstrated that the loosely bound electron in a dipole-bound state occupies a diffuse orbital localized mainly on the positive side of the dipole. 28 This finding was confirmed by many recent studies. The role of non-BO coupling has been studied by Garrett, who concluded that such couplings are negligible for dipole-bound states with electron binding energies (E bind 's) much larger than the molecular rotational constants.…”
Section: Hydrazine and Its Tautomersupporting
confidence: 80%
See 2 more Smart Citations
“…It has been shown that, within the Born-Oppenheimer (BO) approximation, a dipole moment greater than 1.625 D possesses an infinite number of bound anionic states, [47][48][49][50][51] although the more practical critical value required to experimentally observe a dipole-bound anion was found to be slightly larger, about 2.5 D. 43,52 Jordan and Luken demonstrated that the loosely bound electron in a dipole-bound state occupies a diffuse orbital localized mainly on the positive side of the dipole. 28 This finding was confirmed by many recent studies. The role of non-BO coupling has been studied by Garrett, who concluded that such couplings are negligible for dipole-bound states with electron binding energies (E bind 's) much larger than the molecular rotational constants.…”
Section: Hydrazine and Its Tautomersupporting
confidence: 80%
“…The diffuse character of the orbital describing the loosely bound electron (see Figure 2) necessitates the use of extra diffuse basis functions having very low exponents. 28 In addition, the basis set chosen to describe …”
Section: Decomposition Of E Bind Into Various Physical Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jordan and Luken demonstrated that the loosely bound electron in a dipole-bound state occupies a diffuse orbital localized mainly on the positive side of the dipole [17]. This finding was confirmed by many subsequent studies.…”
Section: Dipole-bound Anionssupporting
confidence: 71%
“…The peptide ion dipole was shown to create a 0.4-0.5 V slant in the electrostatic field at distances of 15-20Å from the center of the ion, which can deform the Rydberg orbitals and steer the incoming electron towards regions of higher positive charge density. This is analogous to electron binding to a neutral molecular dipole that was analyzed by Jordan and Luken [75]. However, there is a difference between the ion and neutral dipoles in that electron binding in the ions is primarily due to the strong Coulomb interaction whereas the dipolar field represents an anisotropic perturbation that affects the electron density distribution.…”
Section: Electronic States and Dipolar Field Effectsmentioning
confidence: 99%